Flavanols from the Camellia sinensis var. assamica and their hypoglycemic and hypolipidemic activities - Xin Wang; Quan Liu; Hongbo Zhu; Hongqing Wang; Jie Kang; Zhufang Shen; Ruoyun Chen (Elsevier, 2017)
α-Glucosidase and lipase inhibitors play important roles in the treatment of hyperglycaemia and dyslipidemia.To identify novel naturally occurring inhibitors, a bioactivity-guided phytochemical research was performed on the pu-erh tea. One new flavanol, named (-)-epicatechin-3-O-(Z)-coumarate (1), and 16 known analogs (217) were isolated from the aqueous extract of the pu-erh tea. Their structures were determined by spectroscopic and chemical methods. Furthermore, the water extract of pu-erh tea and its fractions exhibited inhibitory activities against α-glucosidases and lipases in vitro; compound 15 showed moderate inhibitory effect against sucrase with an IC50 value of 32.5 μmol/L and significant inhibitory effect against maltase with an IC50 value of 1.3 μmol/L. Compounds 8, 10, 11 and 15 displayed moderate activity against a lipase with IC50 values of 16.0, 13.6, 19.8, and 13.3 μmol/L, respectively.